
New Member
BODMAS AND SIMPLIFYING AN EXPRESSION
Here is my current matter at hand. The problem below ask me to simplify it and I have no real background with using the B of BODMAS method so I would like you to check out what I have and maybe offer some assistance if you will. Here we go.
5[3(2x2)+3]
=3(x)+3
=6x(5)
=11x
Now this is what I have and I was wondering if I could please get some feedback and direction from someone.
Thanks,
watcjpp

5[3(2x2)+3]
the 2x2 cannot be made to equal x
3(2x2)= 6x 6
then use this back in your equation
5( (6x6) +3)
= 5( 6x3)
=30x 15

New Member
Thanks because I could not find anything that was even close to explaining these operations. I was really thrown off by the Bracket and well I was trying to figure it out.
Again Thanks.
so here we go
5[3(2x2)3]
3(2x2)=6x6
5((6x6)+3)
=5(6x3)
=30x15
Again thanks for the direction once again my headache has been lessened and I learned something new.
Posting Permissions
 You may not post new threads
 You may not post replies
 You may not post attachments
 You may not edit your posts

Forum Rules
Bookmarks